The Political Representation of Minority Group "Ugamo Malim" in Toba Samosir - Simanjuntak, Gabriel Panahatan; Perdana, Aditya (Law Development Journal, 2023)
In formal politics, one of the main issues that is often discussed is the lack of adequate political representation for minority groups. This also has an impact on the emergence of inequality in political policies which affects their level of welfare. This research will discuss the presence of political representation of the "Ugamo Malim" or Parmalim community in the electoral contestation in Toba Samosir Regency in 2009. Representation in this case refers to the presence of someone as a representative of this minority group in the legislative institution through the general election process. Through research using a qualitative approach, this article shows how the political representation of the Parmalim minority community is realized in formal institutional structures and the impact of the presence of Monang Naipospos as a political representative on the Parmalim community. In realizing political representation, it is carried out through a sociocultural approach to attract public sympathy. The presence of Monang Naipospos has had a significant impact as a political representative of minority groups on the Parmalim community itself, as evidenced by improvements to educational facilities for the children of the Parmalim community.